2008
DOI: 10.1007/s10404-008-0296-2
|View full text |Cite
|
Sign up to set email alerts
|

Customized trapping of magnetic particles

Abstract: This paper presents an efficient technique for trapping of magnetic particles in confined spatial locations using customized designs of micro-coils (MCs). Large magnetic field gradients of up to 20 T/mm and large magnetic forces in the range of 10 -8 Newton on magnetic particles with diameter of 1 lm have been achieved using MCs with several planar geometrical configurations. A large magnetic field gradient is generated and enhanced by two structural parameters: the small width and high aspect ratio of each si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…Photolithographic techniques enable fabrication of almost any desired MET geometry; as a result the geometry of an MET can be tuned for a specific application. Ramadan et al [18,[21][22][23][24][25][26][27] and Lee et al [20,28] have demonstrated customized MP traps which emphasize the effects of different MET geometries. Simulations of magnetic fields produced by different MET geometries have magnetic field profiles attributed to the shape of the MET and magnetic coupling between conductors or loops.…”
Section: Geometrymentioning
confidence: 95%
See 1 more Smart Citation
“…Photolithographic techniques enable fabrication of almost any desired MET geometry; as a result the geometry of an MET can be tuned for a specific application. Ramadan et al [18,[21][22][23][24][25][26][27] and Lee et al [20,28] have demonstrated customized MP traps which emphasize the effects of different MET geometries. Simulations of magnetic fields produced by different MET geometries have magnetic field profiles attributed to the shape of the MET and magnetic coupling between conductors or loops.…”
Section: Geometrymentioning
confidence: 95%
“…1) are discussed to illustrate the effect of MET geometry on magnetic field and magnetic gradient [21]. Additional MET configurations exist, but are not described beyond these basic designs.…”
Section: Geometrymentioning
confidence: 97%
“…13 This approach enables dynamic reconfiguration of the magnetic field patterns, but has the drawback of generating Joule heating, which limits considerably the maximum value of generated magnetic field, and thus field gradient, and may have adverse effects on cell viability.…”
Section: B)mentioning
confidence: 99%
“…8,9 However, these techniques make use of external magnets that are difficult to integrate in lab-on-a-chip approaches. Alternatively, current carrying microwires [10][11][12][13][14][15][16][17] or on-chip magnetic patterns in combination with switching external fields [18][19][20] have been employed for localized particle actuation. A very flexible approach to control the position of magnetic particles on a chip without external magnets is given by microwire crossbar arrays as introduced by the group of Westervelt.…”
mentioning
confidence: 99%